Common and Dissociable Neural Activity After Mindfulness-Based Stress Reduction and Relaxation Response Programs. Issue 5 (June 2018) - Sevinc, Gunes; Hölzel, Britta K.; Hashmi, Javeria; Greenberg, Jonathan; McCallister, Adrienne; Treadway, Michael; Schneider, Marissa L.; Dusek, Jeffery A.; Carmody, James; Lazar, Sara W.
ABSTRACT: Objective: We investigated common and dissociable neural and psychological correlates of two widely used meditation-based stress reduction programs. Methods: Participants were randomized to the Relaxation Response (RR; n = 18; 56% female) or the Mindfulness-Based Stress Reduction (MBSR; n = 16; 56% female) programs. Both programs use a "bodyscan" meditation; however, the RR program explicitly emphasizes physical relaxation during this practice, whereas the MBSR program emphasizes mindful awareness with no explicit relaxation instructions. After the programs, neural activity during the respective meditation was investigated using functional magnetic resonance imaging. Results: Both programs were associated with reduced stress (for RR, from 14.1 ± 6.6 to 11.3 ± 5.5 [Cohen's d = 0.50; for MBSR, from 17.7 ± 5.7 to 11.9 ± 5.0 [Cohen's d = 1.02]). Conjunction analyses revealed functional coupling between ventromedial prefrontal regions and supplementary motor areas ( p < .001). The disjunction analysis indicated that the RR bodyscan was associated with stronger functional connectivity of the right inferior frontal gyrus—an important hub of intentional inhibition and control—with supplementary motor areas ( p < .001, family-wise error [FWE] rate corrected). The MBSR program was uniquely associated with improvements in self-compassion and rumination, and the within-group analysis of MBSR bodyscan revealed significant functional connectivity of the right anterior insula—an important hub of sensory awareness and salience—with pregenual anterior cingulate during bodyscan meditation compared with rest ( p = .03, FWE corrected). Conclusions: The bodyscan exercises in each program were associated with both overlapping and differential functional coupling patterns, which were consistent with each program's theoretical foundation. These results may have implications for the differential effects of these programs for the treatment of diverse conditions. Abstract : Supplemental digital content is available in the text.